2008
DOI: 10.1021/jm800704e
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Stabilized Vascular Endothelial Growth Factor-A Antagonists: Synthesis, Structural Characterization, and Bioactivity of Grafted Analogues of Cyclotides

Abstract: Cyclotides are plant derived mini-proteins with compact folded structures and exceptional stability. Their stability derives from a head-to-tail cyclized backbone coupled with a cystine knot arrangement of three-conserved disulfide bonds. Taking advantage of this stable framework we developed novel VEGF-A antagonists by grafting a peptide epitope involved in VEGF-A antagonism onto the stable cyclotide framework. Antagonists of this kind have potential therapeutic applications in diseases where angiogenesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
175
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 52 publications
4
175
0
Order By: Relevance
“…These activities reflect the ability of cyclotides to target cells of different compositions. More than 150 cyclotides have been characterized (10), and their diverse sequences, remarkable stability, and various bioactivities suggest that they have exciting potential as molecular frameworks in drug design (11).…”
mentioning
confidence: 99%
“…These activities reflect the ability of cyclotides to target cells of different compositions. More than 150 cyclotides have been characterized (10), and their diverse sequences, remarkable stability, and various bioactivities suggest that they have exciting potential as molecular frameworks in drug design (11).…”
mentioning
confidence: 99%
“…As another example, it may be possible to optimise the membrane-permeabilizing ability of cyclotides through scaffold modification to efficiently synergise the action of established anticancer drugs, as described above for cliotide CT2 and paclitaxel [68]. Proof-of-concept for such work was recently demonstrated when a grafted cyclotide, showed activity against growth factors involved in angiogenesis [101]; it is well-established that tumor growth is usually associated with unregulated angiogenesis [102]. As further proof-of-concept, more recently, work, which was patented [103], demonstrated that engineered cyclotides were cytotoxic to cancer cells through activation of the p53 tumor suppressor pathway, which is commonly inactivated by these cells to promote survival [104].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the minimal changes introduced in kB1 by SrtA cyclization, no correctly folded peptide was produced when oxidation occurred after cyclization. Small changes in the amino acid composition of cyclotides can have profound effects on the refolding of synthetic forms (6,20), and it is possible that the introduction of the TGGG amino acid sequence in loop 6 of kB1 had a negative effect on the oxidative refolding of the cyclic form. The proximity of the cyclization point to Cys I ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5), the loss of hemolytic activity is presumably due to the effects of the residues introduced into loop 6 upon cyclization. Previous grafting experiments utilizing kB1 have also shown the abrogation of hemolytic activity after relatively minor changes to the primary sequence; for example, the grafting of the vascular endothelial growth factor sequence (RRKRRR) into loop 2, 3, 5, or 6 significantly reduced the hemolytic activity of kB1 (20). The effects of single point mutations on the hemolytic activity of kB1 have also been extensively studied (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation